GDM enhanced acetylcholine induced vasoconstriction in human umbilical vein via CHRM3 and CACNA1C upregulation linked to promoter hypomethylation - Yun He; Qin Ni; Cuiyun Zhang; liulin Zhou; Shuang Li; Yu Tao; Lanhua Liu (Scientific Reports)
Abstract Intrauterine exposure to hyperglycemia increases the risk of hypertension disorders in the offspring. Vascular dysfunction has a critical role in hypertension development. This study aimed to investigate the effects of GDM on human umbilical vein (HUV) constriction and the underlying mechanisms. HUVs were collected from pregnancies with gestational diabetes mellitus (GDM) and healthy normal pregnancies (CON). HUVs were isolated and cut into 4–5 mm lengths, then suspended in 5 mL organ baths. Acetylcholine (ACh, 109-10−4 mol/L) or BayK8644 (specific CACNA1C agonist, 10−9-10−5 mol/L) was cumulatively added into the organ bath to obtain dose-response constrictions. ACh-induced responses were also recorded in the presence of atropine (an inhibitor of muscarinic receptors,10−6 mol/L), pirenzepine (an inhibitor of CHRM1, 10−5 mol/L) AF-DX 116 (an inhibitor of CHRM2, 10−6 mol/L), P-F-HHSiD (an inhibitor of CHRM3, 10−6 mol/L), tropicamide (an inhibitor of CHRM4, 10−6 mol/L), nifedipine (specific CACNA1C antagonist, 10−6 mol/L) or removal of endothelium. Molecular and DNA methylation analyses were utilized to determine molecular pathways in HUVs. ACh and BayK8644-induced vasoconstriction were significantly increased by GDM in HUV. The ACh-induced vasoconstriction was reduced by atropine, pirenzepine, AF-DX 116, P-F-HHSiD, tropicamide, and nifedipine in both groups. Interestingly, after pretreatment with P-F-HHSiD, the difference between the control and GDM groups disappeared, which differs from the effect of other specific muscarinic receptor subtype antagonists. Additionally, removal of endothelium did not significantly affect ACh-mediated constriction in HUV. The mRNA and protein expressions of CHRM1-5 and CACNA1C were significantly increased by GDM. Methylation assay revealed that GDM reduced the methylation levels of the CHRM3 and CACNA1C promoter regions in HUV. GDM increased ACh-mediated vasoconstriction in HUV primarily through upregulation of CHRM3 and CACNA1C, potentially due to decreased methylation levels of their promoter regions.